The Practical Researcher : A Student Guide to Conducting Psychological Research - Dunn, Dana. (Oxford : Wiley-Blackwell, 2010)
In 'The Practical Researcher', Dana S. Dunn's student-friendly writing style and personal tone provide readers with a practical and engaging introduction to research methods in psychology.
The why and how of psychological research -- Research approaches and generating ideas -- Searching and reading the psychological literature -- Writing : a first and last consideration -- Ethical considerations in the practice of research -- Experimental research -- Applied and field research -- Planning analyses and displaying data -- Presenting research -- Closing thoughts and future directions.
Formerly CIP.
Includes bibliographical references and index.
Keywords: Psychology -- Research -- Methodology; Psychology, Experimental